Geographical analysis of environmental distribution of population in Pejwen district Between 1965 and - عبداه, سروە جلال حمه (Sulaimani Journal for Humanities, 2025)
Geographical Distribution of Population in Penjwen District between (1965-2009) is deemed as one of the most important topics within the discipline of Population research as it explores the mutual relationship between the population and their place of inhabitation. This research attempts at explaining the changes the geographical distribution of population of the said district has witnessed between (1965-2009),Moreover it aims to identifying and analyzing the relevant factors that stand behind those changes. Due to the importance of the topic and the strategic impact of Penjwen District location, being adjacent to the Iranian borders, it was one of the main battlefields and the front line in (1980-1988) Iraq Iran war. The district was so influenced by the consequences of that war that, according to the 1987 Census most of its people were displace to other parts of Iraq. The purpose of this study is to show the difference of environmental distribution of population of the aforesaid district, in addition to showing the role of geographical factors in making those differences. In doing so we are mainly motivated by the desire to enable the competent authorities of government to deploy the outcomes of this research in the room of planning and development either on the level of urban areas or rural ones within that district.The rate of urban dwelling inhabitants in Penjwen district in (2009) formed (55%) of the total population of Penjwen, while in (1965) it made up only (21.8%) of its total population. The rate of rural inhabitants in Penjwen district within (1965- 2009) decreased noteabley and only amounted to ( 78.2 %) of Penjwen Population in total,for(1965), but this rate decreased to (45%) in (2009). There appears to be a case of inequality in the environmental Distribution of Population in the districts,as most population have been gathered on a specific point. This needs to be redistributed so as for the distribution to be as equal as it can be.The indications of population change between the urban and rural areas differ from one year to another. This difference appears in the rural areas. As noted, the values of change indications are always positive in urban areas while it takes a negative form in rural areas in some years. The annual volume of increase, on the level of district amounted to (292.8) person in the research period (1965-2009) escalating in the urban areas into (351.9) person and decreasing into (-59.1) in the rural areas. The rate of the district population change for the same period is (%50.79) and the rate of the urban population change reached (279.84) but the rate has reached (13.1-) in the rural areas